2013
DOI: 10.1038/aja.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptors expressed by prostatic stromal cells obtained from younger versus older males exhibit opposite roles in prostate cancer progression

Abstract: Aging is a major risk factor for prostate cancer (PCa), and prostatic stromal cells may also promote PCa progression. Accordingly, stromal cells do not equally promote PCa in older males and younger males. Therefore, it is also possible that the expression of androgen receptors (ARs) by prostatic stromal cells in older versus younger males plays different roles in PCa progression. Using a gene knockdown technique and coculture system, we found that the knockdown of the AR in prostatic stromal cells obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Peritumoral stroma is associated with several tumor-promoting mechanisms, including neoangiogenesis, neurogenesis, remodeling of the extracellular matrix, and induction of epithelial-to-mesenchymal transition [19] . Tissue recombinant experiments have shown that stromal AR expression is necessary for PCa carcinogenesis and tumor growth but that a decreased function of the AR pathway in surrounding stroma promotes tumor aggressiveness [20][21][22] . We also found a lower AR expression in peritumoral stroma in patients with lymph-node or distant metastases compared to those without metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Peritumoral stroma is associated with several tumor-promoting mechanisms, including neoangiogenesis, neurogenesis, remodeling of the extracellular matrix, and induction of epithelial-to-mesenchymal transition [19] . Tissue recombinant experiments have shown that stromal AR expression is necessary for PCa carcinogenesis and tumor growth but that a decreased function of the AR pathway in surrounding stroma promotes tumor aggressiveness [20][21][22] . We also found a lower AR expression in peritumoral stroma in patients with lymph-node or distant metastases compared to those without metastases.…”
Section: Discussionmentioning
confidence: 99%